2003
DOI: 10.1080/08916150390197425
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into Methods of Enhancing Heat Transfer Under Impinging Air Jets

Abstract: Impinging air jets are widely used in industry, for heating, cooling, drying, etc., because of the high heat transfer rates which are developed in the impingement region. In this study, two methods of enhancing jet heat transfer have been investigated, namely, by using turbulence promoters to artificially raise the turbulence level, and by using a loudspeaker to excite the jet acoustically. In both these cases, the increases in heat transfer from enhancement were found to be modest. Some experimental hot-wire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The augmentations reported may be due to combined effect of two factors, namely (a) the enhanced turbulence mixing by distorting the flow fields caused by the presence of ribs and (b) the extension in heat transfer surfaces, fin effect, provided by the ribs. Can and Etemoglu [21] transfer by using turbulence promoters to artificially raise the turbulence level. They observed that the increase in the heat transfer was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…The augmentations reported may be due to combined effect of two factors, namely (a) the enhanced turbulence mixing by distorting the flow fields caused by the presence of ribs and (b) the extension in heat transfer surfaces, fin effect, provided by the ribs. Can and Etemoglu [21] transfer by using turbulence promoters to artificially raise the turbulence level. They observed that the increase in the heat transfer was not significant.…”
Section: Introductionmentioning
confidence: 99%